Fix vs. Float : Evaluating the Transition to a Sustainable Equilibrium in Bolivia - Gonzalez, Andres; Jafarov, Etibar; Rodriguez Guzman, Diego; Walker, Chris (Washington, D.C. : International Monetary Fund, 2022)
Bolivia has achieved noteworthy success over the past 15 years in raising incomes, reducing poverty, and maintaining macroeconomic stability by deploying commodity revenues to finance transfers, public investment, and state-led development, using an exchange rate peg as a policy anchor. However, with the end of the commodity boom in 2014, fiscal deficits have grown and reserves have fallen. One route to restoring long-run sustainability would be to combine fiscal consolidation with a switch to a floating exchange rate. However, a preference for maintaining the peg could be accommodated with adjustments elsewhere in the policy framework. Employing a detailed dynamic stochastic general equilibrium model of the Bolivian economy, this study assesses the long-run sustainability and relative benefits of alternative policy combinations, and calculates optimal adjustment paths for the transition from the present situation to the steady state. It concludes that continued adherence to a fixed-rate regime, while not optimal, is feasible, if supported by a larger fiscal effort.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Current Account Adjustment; Dynamic Analysis; Optimization Techniques; Programming Models; Short-Term Capital Movements